2020
DOI: 10.3389/fpsyt.2020.00322
|View full text |Cite
|
Sign up to set email alerts
|

Memory Retrieval-Extinction Combined With Virtual Reality Reducing Drug Craving for Methamphetamine: Study Protocol for a Randomized Controlled Trial

Abstract: Background: Relapse, often precipitated by drug-associated cues that evoke craving, is a key problem in the treatment of methamphetamine use disorder (MUD). Drugassociated memories play a major role in the maintenance of relapse. Extinction training is a common method for decreasing drug craving by suppressing drug-associated memories. However, the effects are often not permanent, which is evident in form of spontaneous recovery or renewal of cue-elicited responses. Based on memory reconsolidation theory, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 58 publications
1
19
0
Order By: Relevance
“…Disrupted rhythms and frequencies of electroencephalograms can be normalized by neurofeedback rehabilitation, and these clinical effects are sustained (Niv, 2013). Our results on reduced anxiety are consistent with some studies, such as (Khajehpour et al, 2019;Liu et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…Disrupted rhythms and frequencies of electroencephalograms can be normalized by neurofeedback rehabilitation, and these clinical effects are sustained (Niv, 2013). Our results on reduced anxiety are consistent with some studies, such as (Khajehpour et al, 2019;Liu et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…To evaluate the (cost-)effectiveness, relevant RCTs (level VR3), including adequate follow-up periods, need to be conducted. During our literature review, we identified five study protocols that report on planned RCTs and insights into potential new treatment mechanisms [77][78][79][80][81]. The studies focus on approach-avoidance training, mindfulness-based relapse prevention, memory-retrieval extinction and the use of pharmacotherapy (Isradipine) to enhance the effect of VRET on the extinction of craving.…”
Section: Future Outlookmentioning
confidence: 99%
“…Supporting the theoretical significance of memory reconsolidation in the maintenance of substance use disorder, Liu et al describe a novel VR procedure in a study protocol for an upcoming randomized controlled trial with four therapeutic groups (n = 95) [63]. The authors based on previous results hypothesize that adding a reactivation of drugassociated memories 10 min to 6 h prior to exposure may be more effective for reducing craving and cue reactivity than direct exposure.…”
Section: Vr-based Therapeutic Approachesmentioning
confidence: 99%